2015
DOI: 10.2302/kjm.2014-0010-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cerebral Oximetry in Acute Carbon MonoxideIntoxication

Abstract: The purpose of this study was to assess the clinical usefulness of near-infrared spectroscopy (cerebral oximetry) in patients presenting to the emergency department (ED) with carbon monoxide (CO) intoxication. Eighteen patients with a diagnosis of CO intoxication who presented to our ED during 2013 were included in this prospective study. All patients were treated and monitored according to the standard recommendations for CO intoxication. In addition, cerebral oxygen saturation (ScO 2 ) was measured using nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…In the study conducted by Kalkan et al again with INVOS-5100 NIRS device, the pre-treatment ScO2 levels were found to be low and the ScO2 levels after treatment were found to be significantly higher in CO intoxicated patients given NBOT in emergency services. (13). We also found in our study that similar to that of Kalkan et al, but in contrast to Niemann et al's study, the average ScO2 levels of patients treated with NBOT were higher than those of before treatment.…”
Section: Discussionsupporting
confidence: 85%
“…In the study conducted by Kalkan et al again with INVOS-5100 NIRS device, the pre-treatment ScO2 levels were found to be low and the ScO2 levels after treatment were found to be significantly higher in CO intoxicated patients given NBOT in emergency services. (13). We also found in our study that similar to that of Kalkan et al, but in contrast to Niemann et al's study, the average ScO2 levels of patients treated with NBOT were higher than those of before treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Verici dioddan çıkan ışınların alıcı diodlarca algılanması temelinde çalışır. Yani oksijenize hemoglobin ile deoksijenize hemoglobin oranını değerlendirmektedir (8). Oksimetre, dokudaki yakın kızılötesi spektrumdaki ışığın iletimi ve kromoforlarla emilimine dayanır.…”
Section: çAlışma Prensibiunclassified
“…Although there have been many studies of brain tissue oxygenation, the use of NIRS in assessing oxygenation of the intra-abdominal organs and intestines is particularly noteworthy. [2][3][4][5][6] In an experimental study by Gay et al, [7] which evaluated oxygenation of the intra-abdominal organs and intestines in piglets using NIRS, reduced blood flow was reported in the intestine and intra-abdominal organs in animals with induced hemorrhagic shock. No significant difference was determined between invasive methods and NIRS measurements.…”
Section: Introductionmentioning
confidence: 99%